Magnetic Resonance Cholangiopancreatography (MRCP) Images after Black Tea Consumption - Tauqeer Anjum, Shahzeb Mastoi, Aneel Kumar, Jia Dodani, Farah Naz Magsi, Mahnoor Shahzeb (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To evaluate black tea consumption as a negative contrast agent for better imaging of MRCP. Study design: Prospective study. Place and duration of study: Department of Radiology, JPMC Karachi from 1st January 2022 to 30th June 2022. Methodology: One hundred healthy individuals, who volunteered for this research, were provided an informed written consent to sign before their study enrolment. Tea bags from 3 different tea bag companies were used. The efficacy of improvement of MRCP image as a consequence of tea consumption was further noted by a standard procedure. The intensity of signals was measured by circular-ROI (1cm2). The intensity signal was based on noise and measured as signal void. The MRCP results were taken before tea intake after 5 minutes of tea intake and up to 15 minutes were performed. The results were observed through MRCP images. Results: Comparison of visibility in the distal part of the common bile duct by VAS and Likert method showed significant differences before and after the tea consumption and showed better image quality after tea consumption. Comparisons of duodenum and stomach according to VAS and Likert methods were statistically significant. Conclusion: Significant results were obtained after the consumption of black tea for better quality MRCP imaging. Keywords: MRCP; Tea consumption, Better quality imaging; Gastrointestinal system